Molecular Constants of Tricyanomethanide Ion - Kamaraj, V. (Asian Journal of Chemistry, 2010)
Coriolis coupling coefficients, centrifugal distortion constants and thermodynamic functions of tricyanomethanide ion C(CN)3– have been calculated using the force constants evaluated on the basis of General Valence Force Field.